Endothelial dysfunction and cardiovascular risk factors in childhood acute lymphoblastic leukemia survivors. (1st February 2017) - Giordano, Paola; Muggeo, Paola; Delvecchio, Maurizio; Carbonara, Santa; Romano, Alberto; Altomare, Maria; Ricci, Gabriella; Valente, Federica; Zito, Annapaola; Scicchitano, Pietro; Cavallo, Luciano; Ciccone, Marco Matteo; et al.
Abstract: Background: Childhood acute lymphoblastic leukemia (ALL) survivors have increased risk of obesity, metabolic alterations and cardiovascular disease (CVD). Vascular endothelial function has been studied in adult cancers. Limited data exist regarding CVD risk factors among childhood ALL survivors. We aimed to assess endothelial function, metabolic and cardiovascular risk factors in young survivors of childhood ALL. Methods: Auxological parameters, blood pressure, glucose, lipid profile, hemostatic markers (total adiponectin and high-molecular-weight subfraction, endothelin-1, von Willebrand factor antigen, thrombin-antithrombin complex, D-dimers, fibrinogen), high sensitive C-reactive protein and ultrasound parameters of endothelial function (flow-mediated dilation-FMD, common carotid intima–media thickness-C-IMT, and antero-posterior diameter of infra-renal abdominal aorta-APAO) were assessed in 52 ALL survivors and 34 sex and age-matched controls. Results: ALL patients and controls were not statistically different as regards body mass index and waist circumference. Blood pressure, glucose, total and LDL-cholesterol, triglycerides, high sensitive C-reactive protein were statistically higher in ALL than in controls, while HDL-cholesterol was lower in ALL than in controls. Patients showed statistically lower high-molecular-weight adiponectin and thrombin–antithrombin complex ( p  = 0.003 and p  < 0.001, respectively) and higher vonWillebrand factor antigen ( p  = 0.002) than controls. FMD was lower in patients than in controls ( p  < 0.001). Biomarkers of endothelial function, systolic blood pressure and waist circumference were correlated to FMD. Conclusions: ALL survivors showed derangement of endothelial function, which likely occurs during chemotherapy and lasts till follow up. They showed metabolic alterations even though obesity was not documented. Endothelial vascular parameters should be evaluated earlier during follow-up to detect preclinical onset of CVD. Highlights: Childhood ALL survivors show vascular endothelial dysfunction. They show cardiovascular alterations even though obesity is not documented. Vascular dysfunction is expresses by reduction of FMD and of biomarkers (AD/HMW-AD) AD/HMW-AD and FMD detect preclinical metabolic and CV disease in ALL patients. Pharmacological strategies targeting endothelial dysfunction are intriguing.